ONE-DAY WORKSHOP MEMBANGUN NILAI TRUST TERHADAP PRODUK LAYANAN PADA GENERASI Z DI METRO-LAMPUNG - Heri Satrya Wangsa, Ignasius; Josephine Tyra, Maria; Lina, Lina; Riyanto, Agustinus; Gunady Ony, Johan (Universitas katolik Musi Charitas, 2023)
Digital service products require careful attention to the service delivery process and the establishment of trust value. The Community Service Team of Musi Charitas Catholic University Palembang conducted a workshop titled